Investigation on distribution of electro-thermal coupling fields influenced by HVDC bushing insulation properties - Teng, Chenyuan; Ding, Yichao; Zhang, Youbing; Zhang, Yunxiao; Huang, Meng; Zhan, Zhenyu (Frontiers in Energy Research, 2022)
Bushing is an indispensable component in high voltage direct current (HVDC) transmission project. As the main insulating material possesses poor thermal conductivity and negative temperature coefficient (NTC) electrical resistivity, HVDC bushing suffers from the distortion of electro-thermal-coupled fields. Therefore, it is urgent to reveal the influence of electrical resistivity-temperature characteristic and thermal conductivity on the DC electric field distribution within bushing insulation, guiding the design and application advanced insulating materials. Here, the simulation of temperature and DC electric field distribution within a 400 kV bushing are carried out. The results show that the optimization of NTC effect and thermal conductivity of an insulating material is able to obtain a more uniform electric field distribution through homogenizing the electric resistivity distribution within bushing insulation. The activation energy of the insulating material has a similar variation trend with the maximum electric field within bushing insulation, which has a potential to represent the temperature dependence of electrical resistivity of insulating materials. It also shows that the reduction of DC electric field by increasing the thermal conductivity has a saturation feature. As a result, the suppression of the NTC effect should be considered together to obtain a smaller electric field within HVDC bushing. The research study provides a new idea to regulate the DC electric field distribution, which is beneficial to the design of advanced insulating materials.